Periodic precipitation : a microcomputer analysis of transport and reaction processes in diffusion media, with software development - Henisch, Heinz K. (Pergamon, 1991)
Containing illustrations, worked examples, graphs and tables, this book deals with periodic precipitation (also known as Liesegang Ring formation) in terms of mathematical models and their logical consequences, and is entirely concerned with microcomputer analysis and software development. Three distinctive periodic precipitation mechanisms are included: binary diffusion-reaction; solubility modulation, and competitive particle growth. The book provides didactic illustrations of a valuable investigational procedure, in the form of hypothetical experimentation by microcomputer. The development of appropriate software is described and the resulting programs are available separately on disk. The software (for IBM compatible microcomputers; 5 1/4 and 3 1/2 inch disks available) will be sold separately by, The Carnation Press, PO Box 101, State College, PA 16804, USA.